(3GdgjFI GdnqSpfjI aj GdgjFI GdoqSpqfjIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPi YdefG eGde fcf fYde gPG cJGH ai Yde GdgjFI CbJHSJg ef GdBKGQ eG hQO ai GdYQT hGdcQSi s
(3BNQgG (B:s
(3aEPG CQGO Gddg Cf jLQi fjd eUQ CeQ cd fgQ Cf jeOg aGeOJg GdCfgGQ HeGFgG haLQ dg GdCQV YjhfkG aEPG GfJgi ced HMeO Gddg hMSf Jhajbg hMSHfG Gddg hfYe Gdhcjd s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B2047s
Keywords: (3Gdabg GdESdGejs